An integrated design of the photovoltaic-thermoelectric hybrid system. (1st January 2019) - Zhang, Jin; Xuan, Yimin
Highlights: The integrated design is used to improve the PV-TE system. The ceramic plates are removed from the PV-TE system. A V-type groove is used to enhance the absorption of the solar energy. An obvious raise in the efficiency of the PV-TE system is obtained. Abstract: The photovoltaic-thermoelectric hybrid system (PV-TE) has attracted much attention due to its ability of utilizing solar energy in full spectra. This paper uses the concept of the integrated design to improve the PV-TE system. To enhance the heat transfer, the ceramic plates of the commercial TE modules are eliminated from the PV-TE system in order to reduce the thermal resistance. To enhance the absorption of the solar energy, a V-type groove which can keep each PV cell perpendicular to its adjacent PV cells is used in the PV-TE system. An experimental setup is established to demonstrate the feasibility of the structural improvement. The results indicate that the simplified TE structure can lead to an increase in both PV efficiency and TE efficiency by enhancing the heat transfer. An obvious increase in the PV-TE efficiency caused by the V-type groove is observed in the experiment.